Constitutive modeling of shape memory alloys under cyclic loading considering permanent strain effects. (January 2019) - Ashrafi, M.J.
Highlights: Proposing a three dimensional constitutive model for cyclic loading of SMAs. Capable of considering mutual effects of transformation and permanent strains. Elastic and transformation degradation are included in the model. Accurately predicting permanent strain evolution during cyclic loading. Both mechanical and thermal cyclic loadings were studied. Abstract: In many applications of shape memory alloys, the structure experiences a cyclic thermomechanical loading. The present work develops a phenomenological constitutive model for permanent strain evolution in shape memory alloys (SMAs) under cyclic loading. To this end, proper internal variables and material parameters together with free energy and limit function are introduced. The model is able to predict hysteresis loop and its changes by evolution of permanent strain. To show the model capability, we calibrate the model and predict two different sets of experiments. Moreover, the proposed model capability in predicting degradation effects as well as evolution rate and stabilization of permanent strain is carefully studied through several parametric studies. Finally, we show that the model and its numerical implementation is capable in multiaxial non-proportional loadings as well as thermal cyclic loading.